Diagnosis and early intervention, the best strategy for controlling tooth decay in children - Puruncajas-Armas, Carlos A. (2024)
Tooth decay is a widespread disease that damages the tooth and causes pain. Its development is influenced by a complex interplay of factors, including the consumption of cariogenic foods, inadequate oral hygiene practices, and the presence of specific microorganisms. These factors are particularly pronounced in populations with lower socioeconomic status and cultural differences. However, despite various strategics aimed at reducing its prevalence, including those influenced by socioeconomic factors, the effectiveness of these efforts is limited. This results in a decrease in life quality for patients. Therefore, the objective of this research was to explore the effectiveness on diagnosis and early intervention in controlling tooth decay. Through a narrative review of PubMed publications between 2014 and 2023. Using keywords such as diagnosis, intervention, caries, and strategics, we selected twenty articles that met the criteria. The literature analyzed provides evidence of the effectiveness of early intervention in managing the disease, emphasizing the importance of a multidisciplinary approach involving all healthcare personnel, even before the eruption of the tooth. We conclude that clinical visual and tactile diagnosis, combined with early disease management, constitute one of the most accurate strategies for controlling dental decay.